Formulation and Pharmacodynamic Investigations of Lamotrigine Microspheres in Pentylenetetrazole-Induced Seizures in Mice - Taksande, Jayshree B. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Due to the presence of rich blood circulation and non-invasive nature of administration, the nasal route has been established as valuable therapeutic alternatives. This study was designed with the basic objective to formulate mucoadhesive microspheres of anticonvulsant drug, lamotrigine (LT) for intranasal delivery and to carry out its pharmacodynamic investigations to benefit the emergency cases of epileptic seizures. Materials and Methods: The microspheres were prepared by ionotropic gelation method and characterized for morphology scanning electron microscopy, particle size, drug entrapment efficiency, thermal behavior (differential scanning calorimetry), and crystallinity (X-ray diffraction), in vitro swelling studies, in vitro drug diffusion, ex vivo bioadhesion, and ex vivo biocompatibility studies in excised sheep nasal mucosa. The resultant LT loaded chitosan (CH) microspheres were further evaluated for pharmacodynamic efficacy in pentylenetetrazol (PTZ) induced seizures in mice. Result and Discussion: Results demonstrated that the microspheres were discrete, smooth, and spherical in shape with size 24.5 Â± 2.62 to 48.52 Â± 2.34 Î¼m, appropriate for nasal drug delivery. The CH-based nasal LT microspheres demonstrated high encapsulation efficacy, strong bioadhesion potential, and high permeation without any signs of morphological toxicity in excised sheep nasal mucosa. Importantly the intranasal administration of LT microspheres delayed the onset of clonic convulsion and offered complete protection against the PTZ induced seizures in mice compared to its peripheral administration. Conclusion: Thus, the formulation of LT loaded CH mucoadhesive microspheres offers promising advantages over conventional dosage with its immediate onset of action.